2013
DOI: 10.4236/psych.2013.43a041
|View full text |Cite
|
Sign up to set email alerts
|

Different Ways of Perceiving the Aging Process: Social Behaviors of Women and Men in Relation to Age Discrimination

Abstract: Based on the original survey "Relating to Older People Evaluation" (ROPE) by Cherry and Palmore (2008), we have elaborated the instrument Evaluation for Older Adults that consists of 20 items. In this project, we intend on studying the positive and negative behaviors which people have been able to internalize during their daily life, as well as a previous psychometric analysis about the validity of the instrument. The sample is formed by, on one side, students of Psycho pedagogy, and the other side, older stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Adolescents and younger adults reported few ageist behaviours than middle aged and older adults, and women reported more positive ageist behaviours (Cherry et al 2016). Women tended to report less negative ageist behaviours (Shiovitz-Ezra et al 2016) whereas Garcia and Troyano (2013) found no differences between men and women. With 83% of the sample being female, nursing students' ageist attitudes became stronger as their studies progressed (Frost et al 2016).…”
Section: Attitudes Predict Behaviourmentioning
confidence: 99%
See 4 more Smart Citations
“…Adolescents and younger adults reported few ageist behaviours than middle aged and older adults, and women reported more positive ageist behaviours (Cherry et al 2016). Women tended to report less negative ageist behaviours (Shiovitz-Ezra et al 2016) whereas Garcia and Troyano (2013) found no differences between men and women. With 83% of the sample being female, nursing students' ageist attitudes became stronger as their studies progressed (Frost et al 2016).…”
Section: Attitudes Predict Behaviourmentioning
confidence: 99%
“…Generalised discriminative behaviours occurred across all groups: most admitting one or more ageist behaviours (Cherry and Palmore 2008), and ageist attitudes were correlated with negative ageist behaviours (Cherry et al 2015). Whereas Cherry et al (2016) and Shiovitz-Ezra et al (2016) reported more positive ageism rather than negative ageist behaviours; 97.8% reporting they would "hold doors for older people" (Frost el al 2016), and 98% asking "for advice from an older person because of his or her age" (Garcia and Troyano 2013).…”
Section: Attitudes Predict Behaviourmentioning
confidence: 99%
See 3 more Smart Citations